Combinatorial image analysis : 18th International Workshop, IWCIA 2017, Plovdiv, Bulgaria, June 19-21, 2017, Proceedings /: 18th International Workshop, IWCIA 2017, Plovdiv, Bulgaria, June 19-21, 2017, Proceedings. (2017) - Unknown
No abstract available